Propuesta de un plan estratégico que contribuya a la gestión administrativa de la Cooperativa Intercantonal de Transportes Tosagua-Asociada. - Coaboy Zambrano, Erika Tatiana (2018)
The purpose of this research was the proposal of a strategic plan that contributes to the administrative management of the Cooperativa Intercantonal de Transportes Tosagua - Asociada. Internal and external factors were analyzed through surveys applied to administrative personnel, partners and users in order to know the situation in which the institution was located, in that sense it was necessary to identify Strengths, Opportunities, Weaknesses and Threats. Through the PEST analysis, the factors coming from abroad were observed, with regard to the Political, Economic, Social and Technological elements, finding means that contribute and should be contemplated, applied and complied with in order to provide a better service to the users. To establish the strategic direction, elements such as; mission, vision, institutional policies, values, organization chart and strategic objectives, in order to lead the changes in corporate philosophy and its socialization with employees. Likewise, strategies aimed at the search and implementation of initiatives that favor the offer of an adequate service were designed, for which it was pertinent to implement a personnel evolution mechanism, enabling the professional development of employees. With the proposal of a strategic plan for the cooperative, strategic and specific objectives were defined such as planning a system that improves the quality of service and user satisfaction, as well as the development of training programs for administrative personnel, partners and implementation of marketing strategies that allow measuring the situation in which the cooperative is located.